Measuring The Possibility Of Podcasts In Spotify Application To Improve Students’ Listening Skills On Narrative Texts - Disiwi, Nu’mah Fatchiyah; kariadi, mustasyfa thabib; Asriyama, Weksa Fradita (LPPM Universitas Pekalongan, 2023)
This research aimed to improve students’ listening skills using podcast in Spotify application. This research utilized a pre-experimental design with a quantitative approach involving 30 samples of students from MA EL-BAYAN Majenang. The research instruments were pre-tests and post-tets, which consisted of 40 questions based on the application used. The results of this research showed that the students’ listening skill after using podcast in spotify application was improved up to 55.5% from the mean pre-tests score 40.67 to mean post-tests score 63.25. Furthermore, the results of significance values was 0.001 < 0.05, it means that the students’ listening skills using podcasts in Spotify application significantly improved. In other words, Alternative Hypothesis was accepted and Null Hypothesis is rejected. Furthermore, it can be concluded that the use of podcast in spotify application was improve for students’ listening skill on narrative text at grade XI of MA EL-BAYAN Majenang. Based on the research result above, the use of podcast in spotify application was improve for students’ listening skill on narrative text at grade XI of MA EL-BAYAN Majenang. The researcher suggests that the English teachers should use podcast in spotify application for teaching-learning process, especially in listening skill. The researcher also suggests that the student should have more practice in listening skill to improve their abilities. Keywords: Listening Skill, Narrative Text, Podcast in Spotify Application